Uma introdução aos operadores de Schrödinger com ênfase no caso unidimensional. - Ramos, Priscila Santos (2009)
The main objective of this dissertation is to give an introduction to Schrödinger operators of the type H = -∆ + V. In these operators, ∆ denotes the Laplacian of Rⁿ and V denotes the operator of multiplication by a function V both defined in a suitable subspace of L²(Rⁿ) with respect to the determination of its selfadjointess and of its spectrum.